Relationship between Knowledge and Attitude and Community Action in Washing Eating and Drinking Utensils in Togafo Village (International Journal of Scientific Research and Management (IJSRM), 2023)
Poor hygiene of eating utensils plays an important role in the growth and spread of germs and poisoning. Contamination of eating utensils can be caused by germs, poor washing processes and poor handling after the washing process. This research aims to determine the relationship between knowledge and attitudes regarding community actions in washing eating and drinking utensils in Togafo Village. The type of research used is analytical observational research using a cross sectional design. The types of data used in this research are primary and secondary data. Data analysis was carried out using univariate and bivariate methods. The results of the research showed that respondents with good knowledge (21.7%) and less knowledge (30.0%) were not much different from respondents with good actions (washing techniques) and the results of the analysis also showed that there was no significant relationship between knowledge and action. Respondents with good attitudes (16.7%) and less knowledge (44.4%) in respondents with good actions (washing techniques) are quite different and the results of the analysis also show that there is a significant relationship between knowledge and action (p value <0 .05). Advice to the public to maintain and not ignore appropriate and appropriate washing techniques, such as flushing, washing, rinsing, to avoid germs that exceed standards on eating utensils.